JURIDICAL ANALYSIS OF THE CRIME OF EMPLOYMENT IN THE POSITION BY THE CASHIER AND ADMINISTRATIVE OFFICERS CV. RAJAWALI MAS PERKASA IN CASE NO. 49/PID.B/2016/PN.PBR - Amri Albadru Lopa (Jurnal Multidisiplin Sahombu, 2021)
Crimes and violations are complex phenomena that are understood from various different sides, so that comments or opinions about a crime and violation are often different from one another. Therefore, the legislators in this country focus on making and implementing regulations that apply to crimes and violations that arise against public order, scientific facts, criminal acts of decency, and crimes that threaten the security of the State in case No.49/Pid. .B/PN.Pbr. The main method in this study aims to find out the evidence of the elements of a criminal act imposed in the decision No.49/Pid.B/2016/PN. Pbr and to find out what is the basis for judges' considerations in imposing criminal charges against defendants of embezzlement in office by cashiers and administrative officers CV. Rajawali Mas Perkasa. The research used is library research and field research with descriptive research type, namely analyzing data obtained from field studies and literature by explaining and describing the reality of objects. The approach to the problem is carried out in a juridical manner, namely a study of the laws and regulations. The data used are primary data obtained directly from the object of research in the field and secondary data obtained from the results of library studies. This research was conducted at the Pekanbaru District Court. The result of this research is that it is known that the evidence for the elements of a criminal act applied in the case of Decision No.49/Pid.B/2016/PN.Pbr. evidence. The defendant was charged with committing a criminal act of embezzlement in office as contained in Article 374 of the Criminal Code and Article 372 of the Criminal Code. Knowing the basis of the judge's consideration in imposing a crime against the defendant of embezzling CV. Rajawali Mas Perkasa, where in this case the panel of judges decided that the defendant was proven to have violated the indictment of Article 374 of the Criminal Code regarding embezzlement, the panel of judges gained their conviction by emphasizing the legal values of the trial process, namely the evidence and facts revealed in court.